An electrochemical sensor based on PANI-Ag1-x-Fex nanocomposite thin films irradiated by 10 kGy of gamma ray for E. coli detection applications. (16th April 2022) - Abdullah, Huda; Kamarudin, Muhamad Aiman; Mohammad Naim, Norshafadzila; Abdul Hamid, Aidil; Hafiz Dzarfan Othman, Mohd
ABSTRACT: The synthesis of PANI incorporated with Ag-Fe in nanocomposite thin films-based electrochemical sensor was developed by irradiating with 10 kGy dose of gamma ray. PANI-Ag-Fe nanocomposite was synthesised by oxidative polymerisation process from aniline. The films was deposited using spin coater with sol-gel method before being irradiated with 10 kGy of gamma ray. The characterisation of PANI-Ag-Fe films with various concentrations of Ag-Fe was investigated using XRD, FESEM and UV-Vis spectroscopy. The sensor performance was measured using I-V measurement. The sensitivity of sensor was tested upon pure water and E. coli solution. XRD analysis shows that the crystallite size decreases with the rise of Fe concentration. FESEM images show the nanostructure of Ag-Fe particles in dendrite and spherical shape. UV-Vis absorption peaks appeared in between 420 and 450 nm wavelengths. For sensor performance, I-V characteristic and impedance analysis show PANI-Ag-Fe with highest concentration of Fe performed higher sensitivity towards E.coli presence. GRAPHICAL ABSTRACT: uf0001